EFFECT OF IN VITRO CULTIVATION ON THE PATHOGENICITY OF WEST NILE VIRUS - Koprowski, Hilary (The Rockefeller University Press, 1946)
The West Nile virus was cultivated in suspended cell culture media employing several different tissue components, and it has been observed to survive in culture for at least 32 days. Continued propagation of the virus in vitro resulted in a change in its pathogenicity. The change lay in a marked reduction or a complete loss of the ability of the virus to produce fatal infections in mice and in hamsters on peripheral inoculation, although there was no obvious simultaneous alteration in the lethal effect of the virus by the cerebral route. In mice, the extent to which invasiveness was lost depended upon the passage level of the virus and the age of the test animals. The younger (and more susceptible) the mice, the greater the number of passages which was required to diminish the virulence of the virus by peripheral routes; after 68 passages, the virus still retained its full capacity to kill 3-day-old mice, while its ability to kill 8-day-old mice was reduced and its ability to kill mice 14 or more days of age was essentially abolished. How soon the loss of pathogenicity occurs in hamsters has not been determined. Prolonged cultivation rendered the virus avirulent for hamsters by the intraperitoneal route.